2019
DOI: 10.1038/s41598-019-52736-y
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin Alleviates Steatosis and Fibrosis in Mice with Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) is the most severe and progressive form of nonalcoholic fatty liver disease (NAFLD), which can lead to life-threatening conditions, however, there is still no approved drug for the treatment of NASH. In this study we used human-like NASH mouse model and treated orally with isorhamnetin at a dose of 50 mg/kg to analyze the effect of isorhamnetin on the progression of NASH. NASH-induced mice represented severe steatosis with inflammation, and fibrosis in liver accompanied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…In the present study, we have evaluated the cardioprotective potential of ISO in hAESCs. Previously, we have reported that ISO, a flavonol, alleviates hepatic fibrosis in NASH model mice (Ganbold et al, 2019). Although several flavonols have been reported to improve cardiac dysfunction and fibrosis (Suzuki et al, 2007;Li et al, 2013;Geetha et al, 2014;Guo et al, 2015;Zhang et al, 2018), very little is known about the effect of ISO on cardiac hypertrophy and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we have evaluated the cardioprotective potential of ISO in hAESCs. Previously, we have reported that ISO, a flavonol, alleviates hepatic fibrosis in NASH model mice (Ganbold et al, 2019). Although several flavonols have been reported to improve cardiac dysfunction and fibrosis (Suzuki et al, 2007;Li et al, 2013;Geetha et al, 2014;Guo et al, 2015;Zhang et al, 2018), very little is known about the effect of ISO on cardiac hypertrophy and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has anti-inflammatory, antioxidant, antiadipogenic, and antitumor activities (Hu et al, 2015;Yang et al, 2016). We have previously reported the anti-oxidant, antiobesity, and antifibrotic effects of ISO in rodent models (Zar Kalai et al, 2013;Ganbold et al, 2019). Ganbold et al (2019) reported that ISO could alleviate steatosis and fibrosis in a non-alcoholic steatohepatitis (NASH) mouse model by reducing the expression of liver injury marker transforming growth factor β (Tgf β), and the fibrogenic marker Collagen type I alpha 1 (Col1a1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies on the impact of luteolin in a more chronic model of liver fibrosis are desired, these data pointed towards therapeutic application of this drug in patients with hepatic fibrosis [97]. Similarly, in a study of Ganbold et al [3], it was recently shown that administration of isorhamnetin, another natural flavonoid to human-like NASH mice, resulted in improved steatosis, liver injury, and fibrosis, pointing towards its therapeutic potential in NASH.…”
Section: Therapeutic Approaches In Preclinical Nafld Modelsmentioning
confidence: 99%
“…If steatosis is not managed in time, resident liver cells (e.g., Kupffer and hepatic stellate cells) become activated and immune cells (mainly macrophages) infiltrate the liver, a condition defined as NASH. This progressive form of NAFLD [3] can further trigger hepatocyte damage with/without fibrosis and increase the risk of cirrhosis [4] and hepatocellular carcinoma (HCC) [5]. In contrast to alcoholic liver disease-and viral hepatitis-induced HCC, NASH-related HCC is currently the most rapid growing indication for liver transplant in HCC patients [6].…”
Section: Introductionmentioning
confidence: 99%